Water quality awareness and barriers to safe water provisioning in informal communities: A case study from Ndola, Zambia - Liddle Elisabeth S.; Mager Sarah M.; Nel Etienne (Bulletin of Geography. Socio-Economic Series)
Local water providers in developing nations typically view shallow hand-dug wells as traditional and backward sources of water supply. It has long been assumed that the urban poor do not have the ability to develop these in a way that allows them to be classified as ‘improved’ in terms of the Millennium Development Goal for water, believing that users do not understand the factors that constitute safe water and the threats to these sources. Our assessment of the level of environmental knowledge held by local water-users in Ndola in Zambia demonstrates a coherent understanding of the safety of their water sources, the quality of these, the threats to them, and the fundamentals of how their local hydrology works, all of which is contrary to the perspective of key informants who are involved in water supply. Despite their environmental awareness, the majority of users did not generally protect their wells from contamination nor treat their water. The apparent paradox between awareness of risks to water and implementing protection of that water source is a function of the complex suite of socially manifested attitudes, habits and behaviours when it comes to water protection and treatment, which is exacerbated by vulnerable community and family structures and entrenched poverty. For meaningful outcomes in improved access to safe water to be realised providers need to increase their engagement with the informal communities, moving deeper into community-based participatory planning and recognise the societal and cultural factors that are entrained into these communities water supply practices. A key part of this involves the need for providers to move away from simple knowledge-based education to the more holistic form of skill-based health education.